The 13-minute murder [compact disc, unabridged] - Patterson, James, 1947-; Farnsworth, Christopher; DiLallo, Max; Serafin, Shan, 1982-; Serafin, Shan, 1982- (Hachette Audio, 2019)
In three short-story thrillers, a psychiatrist, a mother, and a hitman all must save high-stakes crimes against different ticking clocks.